Ética na empresa: reflexões sobre o indivíduo e suas relações no trabalho. - Rezende, Frederico Pifano de (2003)
Ethics has gradually becoming an object of great interest and methodical study on the part of researchers and professionals in the area of Business Administration. Under various denominations and different concepts, ethics has been the target of investiga